Exploring the impacts of China’s water resource tax policies: A trade-off between economic development and ecological protection - Xin, Chunhua; Guo, Fengqi; Wang, Anqi (Frontiers in Environmental Science, 2022)
The reform of water resource tax policies is an important measure in the process of China's green economic transformation. Therefore, improving the accuracy of tax policy impact prediction is crucial for policy makers to make correct decisions. This study focused on the water resource tax policies composed of water resource tax and water pollution tax. A WCGE (water computable general equilibrium) model extended from the traditional CGE model was proposed to simulate the impacts of policy changes and determine the optimal tax rate range. Water self-purification capacity and agricultural subsidies was first considered in WCGE, providing a simulation-evaluation method that could support the analysis of policy alternatives from a more realistic perspective. The results indicated that water resource tax and water pollution tax synergistically promote water conservation and water pollution reduction, and the negative impact on the economy when they are raised together is lighter than that when the tax burden is raised alone. The water resource tax has the best water saving effect, but also has the greatest negative impact on the economy. Technological progress has the best effect in reducing water pollution and is also conducive to reducing the adverse impact of tax increases on the economy. Taxation can also improve social welfare and the optimal tax rate level is the combination that water resource tax is 4 yuan/m3, and the water pollution tax is in the range of 5.6-8.4 yuan/pollution equivalent. The results demonstrate the positive role of government in environmental governance and provide a scientific basis for policymakers to adjust the direction of policy reform, strengthen the collaborative design of water tax policies and select the optimal tax rate level. As well, solutions of WCGE could provide in-depth analysis of the trade-offs between violation risk and system benefits and generate more reliable results by reproducing actual situations. Moreover, the WCGE model constructed in this study is also applicable to analyze other types of policies.